Entre cinema e pintura: o realismo plástico de Stanley Kubrick em Barry Lyndon - Ezequiel, Maíra Cínthya N. (2007)
This investigation searches for the effects of meaning resultants from the use of plasticity as a method for creating the visuality in the movie Barry Lyndon, by Stanley Kubrick (1975), and, at the same time, the intersemioticity that emerges from the blending of the aesthetic languages of cinema, painting and literature here involved. Concerning the methodology, it is based on a group of aesthetic and semiotic theories which include, especially, the model for analysis of meaning in visual arts proposed by Erwin Panofsky, the bonds between cinema and painting noted by Jacques Aumont, the concept of effect of realism such as formulated by Roland Barthes and of intersemiotic translation introduced by Roman Jakobson (and later redeveloped by Julio Plaza). The aim of this research is to follow the process of production of a realistic effect on the passages between one language and another. The hipothesis risen is that the strong sense of verosimilitude that results from the final product borrows its mode of installation from some of the eighteenth century realistic French painting. The choice of the movie is due to its stated visual exuberance as a result of a sophisticated dialogue established between the careful light capture and the rigorous use of pictorial references in correspondence with the historical time of the action, precisely the works Constable, Courbet, Corot and the so-called Barbizon Painters. Finally, Por fim, it drafts na approach between Kubrick s work and the idea of Modernity as thought by Baudelaire